Second Chances : Surviving AIDS in Uganda - Whyte, Susan Reynolds (Book collections on Project MUSE., 2014)
During the first decade of this millennium, many thousands of people in Uganda who otherwise would have died from AIDS got second chances at life. The essays in Second Chances draw on personal accounts and a broad knowledge of Ugandan culture and history to explore antiretroviral therapy from the perspective of those people.